Statistics: more regression models. (4th October 2013) - Scott, M.; Flaherty, D.; Currall, J.
Abstract : In a previous article, we tackled the question "How are we related?" for the simple case of one explanatory variable or covariate. Now we can move onto a natural extension, with still only one response variable, but more than one explanatory variable.